Metallographic analysis of a TRIP 800 steel using digital image processing - da Costa, Fernando Henrique [UNESP]; Fukugauchi, Cristina Sayuri [UNESP]; dos Santos Pereira, Marcelo [UNESP] (Trans Tech Publications, 2015)
In the second half of the last century, the automobile industries were affected from the petroleum crisis caused mainly by the wars in the Middle East. These crises led the automakers reconsider their vehicles. One of the most important events after that was the adoption of new steels by the industry. One example is the TRIP steels (Transformation-induced plasticity). In this work, a specimen of TRIP steels was etched using LePera reagent. The obtained images were analyzed using digital processing. Using the ImageJ software the methods threshold and watershed were studied. The methods were compared: the morphological characteristics and volumetric fraction of the retained austenite and martensite phases were analyzed. The results showed that the threshold led to a higher number of identified grains with lower mean area and total area fraction than the watershed method.
Keywords: Image processing; LePera; Threshold; TRIP; Watershed